Approaches to gender-based violence and legal abortion in health services during COVID-19 lockdown - Lorena Saletti-Cuesta; Lila Aizenberg (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
This study is interested in analyzing how health services address gender-based violence and legal abortion in a context of mandatory preventive social isolation. Between May and June 2020, 27 telephone interviews were conducted with healthcare professionals and key informants from Córdoba and Resistencia. Changes in detection, methods, and demand were identified, related to the reorganization of the healthcare system, modifications in the care relationship, and the resources needed to respond to demand. The pandemic has deepened barriers to women's access to health services and has added new ones. Networks among healthcare professionals, feminist healthcare practices, and innovative approaches were identified as facilitators of access, which have been central in mitigating the effects of the pandemic and guaranteeing rights.